Pengaruh Bunyi Kadazandusun Terhadap Kesempurnaan Bacaan Al-Fatihah - Mohd. Taqwudin Bin Mohd. Yazid; Mohammad Najib Jaffar; Mohd Nizwan Musling; Norazman Alias; Mohamad Ali (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia